The Importance of Social Status in a Rent-Seeking Society - J. Atsu Amegashie (Center for Economic Studies and ifo Institute (CESifo), 2024)
Status-seeking exists in all societies but different societies value status differently. How does the importance of social status affect the mode of status-seeking? I consider a game in which status can be achieved through productive effort that increases wealth or through a contest in which unproductive (rent-seeking) effort is used to redistribute wealth. Contestants are identical and there is a constraint on total effort. The number of contestants, the security of property rights, and the opportunity cost of unproductive activities in terms of productive activities (i.e., when the constraint binds or does not bind) determine whether an increase in the importance of status leads to an increase or decrease in productive effort (economic output). When the constraint on total effort does not bind, an increase in the importance of status leads to an increase in rent-seeking effort, regardless of the security of property rights. When the contestants differ by their taste for status, status-seeking can have far-reaching effects as a few people become more status-conscious and increase their status-seeking effort, this causes other relatively less status-conscious people to respond. When the contestants have different productive abilities, there exists an equilibrium in which rent-seeking effort is independent of productive ability.
Keywords: C72; D72; 330; contest; productive effort; property rights; rent-seeking; status-seeking